2021
DOI: 10.1111/obr.13405
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational transmission of obesity: A systematic review and meta‐analysis

Abstract: There is a strong link between parental and offspring obesity status. However, the state of epidemiological evidence on multigenerational transmission of overweight/ obesity, such as from grandparents to grandchildren, is relatively unknown. This systematic review collates and appraises existing evidence on multigenerational transmission of overweight/obesity and uses meta-analytic estimates for quantitative synthesis. Six electronic databases were searched for publications reporting the relationship between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…For instance, in the study, the presence of obesity in the family was found to be one of the factors that predicted obesity in children. This finding is also in line with the meta-analysis findings in the literature ( 67 , 68 ). On the other hand, in a study involving 3,963 children and parents, Savaşhan et al ( 69 ) found that 64.9% of parents of obese children were pleased with their child’s weight.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in the study, the presence of obesity in the family was found to be one of the factors that predicted obesity in children. This finding is also in line with the meta-analysis findings in the literature ( 67 , 68 ). On the other hand, in a study involving 3,963 children and parents, Savaşhan et al ( 69 ) found that 64.9% of parents of obese children were pleased with their child’s weight.…”
Section: Discussionsupporting
confidence: 92%
“…There were also studies claimed that grandparents' obesity condition might have an impact on grandchildren's obesity either directly by grandparents to shape grandchildren's behavioral decisions or indirectly by their parents. 54,55 Golding et al demonstrated that when both grandmother and mother had smoked, compared to mothers who had not smoked, the smoking ones' female descendant had declined in height, weight, and fat/ lean/bone mass. 56 And the Framingham Heart Study demonstrated that grandparents who had hypertension in early life could increase the hypertension risk among grandchildren after adjusting for parental confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…The number of papers investigating the issue of inadequate maternal BMI and its consequences in children clearly indicates that this topic has gained interest. The issue of parental obesity may be of even greater public health concern as there are animal studies [ 12 , 60 ] and epidemiological studies [ 61 ] reporting multi-generational adverse effects of excess body weight. Most of the data confirms significant adverse neurodevelopmental outcomes in children caused by MOv/MOb and/or excessive GWG.…”
Section: Discussionmentioning
confidence: 99%